2017
DOI: 10.29252/nrip.irj.15.3.207
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Challenges of Physiotherapy Clinical Education: A Qualitative Study

Abstract: Objectives: Clinical education is an important component of physiotherapy education. The students' and clinical educators' viewpoints about different aspects of education are being analyzed worldwide for the promotion of educational services. The aim of this study was to identify the challenges of clinical education based on the experiences of physiotherapy students and educators.Methods: A qualitative study was conducted using content analysis method. Data were collected through semi-structured interviews usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The negative effects of senior students on other students and their pessimism and disappointment are in line with the results of this study. However, a number of studies have explained how a positive relationship between peers improves the learning process [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative effects of senior students on other students and their pessimism and disappointment are in line with the results of this study. However, a number of studies have explained how a positive relationship between peers improves the learning process [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical educators identified a range of characteristics exhibited by their students, including interest, motivation, attitude, and desire to perform technical work affecting the student's active presence in clinical settings. Studies have reported that lack of student motivation to learn, and their irresponsibility and irregularity, affect clinical education [24,29].…”
Section: Discussionmentioning
confidence: 99%
“…Chiang and Sloan in similar studies have argued that clinical proficiency, the ability to transfer skills to students, responsibility, effective communication with students, and adherence to the clinical ethics, are facilitators of clinical education [10,16]. To make the clinical education more effective, students also need to have features like willingness to learn, responsibility, high self-confidence, a sense of compassion and sympathy, sufficient information and a spirit of partnership with the supervisor [1,4,5,11].…”
Section: Discussionmentioning
confidence: 99%
“…Another barrier to the efficiency of clinical education was the lack of adequate supervision over the performance of clinical educators and the implementation of training programs in clinical settings. Other studies have also reported that monitoring and evaluation is an important indicator in the measurement of achievement to educational goals, because it determines the strengths and weaknesses of training program [1,3,5,20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation